A comparison of fatigue removal speed for some physiological and biochemical indicators of Fencing and Arab sword players - Ghaleb Oudah, Ishraq (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at the development of a scientific basis is correct when selecting some means of training to remove fatigue through the use of the proper exercise of calm during the training dose during the iterations of these means working to help the player to get rid of the effects of fatigue, including a n game fencing is located within the mixed system with the beat anaerobic system by more of the antenna system, so it requires the development of energy systems for players n and the ability to withstand high levels of acid to your children in the muscles and blood and increase the associated pain as a result of fatigue that occurs during the performance , research methodology: the Choose the sample purposively team players young people to Epee totaling ( 5 ) player, and team players the sword of the Arab and the number ( 5 ) player , used tests look first : the equation of fatigue, pulse rate at rest and after effort, measuring the concentration of acid , lactic in the blood after the effort, the tests Alp a Yukemiaiah Second test of urea , testNa, Test KTest CL, Test PhosphorusIt has been conducting tests of the variables surveyed after the training program finishes were accreditation training program prepared by the coach , and after collecting the results used researcher bag statistical to interpret the results , concluded the researcher Th : players Epee preference in the index of muscular fatigue tests , pulse rate at rest and after rest, and measure L- benic acid for the benefit of the Arab sword group within physiological indications and tests ( urea test, test Na, Test K. Test CL, Test Phosphorus) Within the biochemical indicators for the Epee group recommends a researcher of : the need to emphasize the training programs and rapid removal of fatigue dissuading periods of numbers , public and private competitions.